Experimental study of heat transfer between thin liquid films flowing down a vertical string in the Rayleigh-Plateau instability regime and a counterflowing gas stream. (May 2017) - Zeng, Zezhi; Sadeghpour, Abolfazl; Warrier, Gopinath; Ju, Y. Sungtaek
Highlights: The liquid mass flow rate, air velocity and nozzle radius influence the radius and spatial/temporal frequency of liquid beads. The liquid flow rate and air velocity are the two primary factor affecting heat exchanger effectiveness rather than liquid flow patterns. The liquid flow pattern only affects the individual bead-to-air heat transfer coefficient. Abstract: Direct contact heat exchangers based on wetted string columns offer an intriguing alternative to packed beds and spray columns. We experimentally examine the flow and heat transfer characteristics of thin liquid films flowing down strings of a diameter approximately 1 mm against a counterflowing air stream. Numerical simulations are also performed to help interpret and validate our experimental results. The Rayleigh-Plateau instability caused by interplay among surface tension, gravity, and viscous forces leads to the formation of uniformly spaced drop-like liquid beads traveling down a string. The liquid mass flow rate and also the nozzle radius influence the radius and spatial/temporal frequency of liquid beads. Aerodynamic drag exerted by the counterflowing air stream deforms liquid beads. The relationship between flow characteristics and heat transfer effectiveness are examined experimentally for different combinations of the air velocities, liquid mass flow rates, and nozzle radii. We show that the liquid mass flow rate and the air velocity are two primary factors influencing heat transfer effectiveness whereas details of the liquid flow instability affect local bead-to-air heat transfer coefficients. We also compare the heat transfer effectiveness and the pressure drop between a wetted string column that consists of an array of vertical strings and a well-established structured packing that consists of vertical plates. The wetted string column is shown to deliver comparable heat transfer performance but at a lower air pressure drop than the structured packing. The present work helps improve our understanding of the flow and heat transfer performance of string-based direct-contact heat exchangers and helps build a foundation for their systematic design and optimization.